2012
DOI: 10.4103/0257-7941.118547
|View full text |Cite
|
Sign up to set email alerts
|

Ethnozoology of the Karbis of Assam, India: Use of ichthyofauna in traditional health-care practices

Abstract: Background:Traditional or folk medicine is still prevalent among the Karbis as means of primary health-care. Traditional medicine is not only a source of healing, but the practice is also an important part of their religion and culture.Aim:The aim of the present study is to discuss the use of ichthyofauna in traditional health-care practices among the Karbis and other ethnic tribes of Karbi Anglong district, Assam.Setting and Design:Field study was undertaken from March 2011 to June 2012. A total of 75 informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…All Karbis irrespective of their financial status prefer foods cooked without oil. Teronpi et al [6] studied indigenous knowledge of management of fish resources and revealed that hill Karbis cook fish by kangthu and kemang method. A study conducted by Muzaddadi et al [7] mentioned in a study of ethnic fish product prepared by Mishing tribe of Assam that food processing techniques like drying, smoking and fermentation are compatible means of preserving fish for scare fish seasons and a partial solution to protein malnutrition.…”
Section: Cooking Methods Among the Karbismentioning
confidence: 99%
“…All Karbis irrespective of their financial status prefer foods cooked without oil. Teronpi et al [6] studied indigenous knowledge of management of fish resources and revealed that hill Karbis cook fish by kangthu and kemang method. A study conducted by Muzaddadi et al [7] mentioned in a study of ethnic fish product prepared by Mishing tribe of Assam that food processing techniques like drying, smoking and fermentation are compatible means of preserving fish for scare fish seasons and a partial solution to protein malnutrition.…”
Section: Cooking Methods Among the Karbismentioning
confidence: 99%
“…Our study focussed on three of the predominant indigenous tribes of Assam State in Northeast India: (1) Biate; (2) Dimasa; and (3) Karbi. These tribes are characterised by unique traditions and cultures distinct from each other and from other ethnic groups of the region (Teronpi et al 2012). However, broadly speaking, subsistence agriculture or hunting and gathering are practised by rural villagers belonging to all three groups (Sajem and Gosai 2006).…”
Section: Study Areamentioning
confidence: 99%
“…A deep faith in, and preference for, their traditional healthcare system (based on surrounding flora and fauna) rather than the modern system of medicine has been reported across all three groups (e.g. Sajem and Gosai 2010, Teronpi et al 2012, Betlu 2013. Similarly, although they are known to practise traditional religion (that is animistic in nature) to varying degrees, the prevalence of associated rituals has been affected by the advent of Christianity across all three groups (e.g.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The medicinal species collected in this study are not used in remote areas of the northern hemisphere, but if they are employed species belonging to some documented genera. In India the eel ( Anguilla bengalensis in this case) is used: its body mucus is applied on burned zones of the body [ 117 ], and fat is applied and massage to relieve rheumatoid-arthritis pain [ 118 ]. In the same way, at Jeju Island (Korea) the salted heads of Engraulis japonica are used to treat head lacerations [ 119 ].…”
Section: Resultsmentioning
confidence: 99%